Analisis Metode Underwriting Untuk Meningkatkan Peserta Asuransi Jiwa Syariah (Study Kasus AJB Bumiputera 1912 Cabang Medan) - Tambak, Ayub; Batubara, Maryam; Syahbudi, Muhammad (Universitas Labuhanbatu, 2023)
This research was conducted at Ajb Bumiputera 1912 Syariah Medan Branch. The type of research used is descriptive qualitative using primary data, namely field research, using document study tools, interviews and observations. the last step of the research is data analysis. The purpose of this research is to explain the factors considered in the process of selecting prospective customers by looking at the contribution of age, gender, work and hobbies, while for the company's strategy to increase sharia life insurance participants it is necessary to prepare human resources life skills in the world of insurance marketing, and the methods used to classify all the factors considered by the company's Underwriters, namely the four methods of Manual underwriting, Experience Underwriting, Blended Underwriting, and Forcasting.